Monopsony and Employer Misoptimization Explain Why Wages Bunch at Round Numbers - Dube, Arindrajit; Manning, Alan; Naidu, Suresh (American Economic Review, 2025)
We show that administrative hourly wage data exhibit considerable bunching at round numbers. We run two experiments randomizing wages around $0.10 and $1.00 to experimentally measure left-digit bias for identical tasks on Amazon Mechanical Turk; we fail to find any evidence of discontinuity in the labor supply function at round numbers despite estimating a considerable degree of monopsony. We replicate these results in administrative worker-firm hourly wage data from Oregon. We can rule out inattention estimates found in the behavioral product market literature. We provide evidence that firms “misoptimize” wage setting. More monopsony requires less employer misoptimization to explain bunching. (JEL D22, J22, J31, J42)